A stochastic optimization model for aircraft scheduling under uncertainty during operational times (2017)
The variability in operational times in the preparation and execution stages of a flight has a significant impact on aircraft scheduling, causing delays and influencing the performance of aerial operations. The present work analyzes aircraft scheduling, from the perspective of the Fleet Assignment to different flights, considering the stochastic behavior of operational times and modification in departures and arrivals for an itinerary in a daily operation. The modification of different schedules is subject to proposed time windows, for a flight to be delayed or anticipated, guaranteeing greater flexibility and operation robustness. To solve the Fleet Assignment Problem, a stabilized column generation problem is used, applying a set of specialized auxiliary shortest path models, based on linear programming. Finally, using a Monte Carlo simulation, the On - Time Performance of the fleet assignment is evaluated in specific scenarios considering the weather effect.